Allergic-like disorders and asthma in patients with common variable immunodeficiency: a multi-center experience. (15th February 2022) - Rubin, Limor; Shamriz, Oded; Toker, Ori; Kadish, Ela; Ribak, Yaarit; Talmon, Aviv; Hershko, Alon Y.; Tal, Yuval
Abstract: Objective: Common variable immune deficiency (CVID) encompasses a variety of diseases characterized by disturbed immunoglobulin (Ig) production and various immune dysregulations. Scarce data are available regarding relationships between CVID and allergic diseases. Here we examined possible associations between allergies and CVID. Methods: For this multicenter study, we prospectively enrolled 79 adult CVID patients (≥18 years) who were diagnosed and treated between 2002–2017 at the Hadassah-Hebrew University and Shaare Zedek Medical Centers, Jerusalem, Israel. These patients were examined for allergic manifestations. Patient evaluation comprised medical history, physical examination, skin allergen testing, complete blood count, serum immunoglobulins, IgE levels, and pulmonary function tests. Results: After implementing exclusion criteria, 29 patients were included in the final analysis. Allergic-like disorders were diagnosed in 65% of CVID patients with non-elevated serum IgE levels. Moreover, allergic CVID patients exhibited a higher prevalence of bronchiectasis on chest CT. Autoimmunity was diagnosed in 41.3% of CVID subjects. The type I allergy detected in our study was non-IgE mediated. Conclusions: Timely diagnosis and stratification of allergy in CVID patients is expected to improve their outcome and quality of life, as well as promote appropriate treatment and better management of pulmonary exacerbations.